Système et crise en politique internationale - Brecher, Michael (Études internationales, 1984)
This paper is designed to enrich basic concepts. The specific goals are twofold: to stimulate a renewed interest in a System orientation to international relations ; and to prepare the g round for an analysis of the system-crisis linkage, that is, crises as international earthquakes or triggers to System change. The first section analyses approches to international Systems. In the light of their shortcomings a revised definition of a System is presented, along with a discussion of the core System components - structure, process, issue, boundaries, context and environment. The second part attempts to break fresh ground on the concepts of stability and equilibrium. The third section provides a new perspective on systemic crisis. Part four confronts the major task of linking the unit and System levels of crisis analysis, conceptually and empirically.